Mali: Impacts of the Ukraine and global crises on poverty and food security - Xinshen Diao; Dorosh, Paul A.; Randriamamonjy, Josee; Smart, Jenny; Thurlow, James (International Food Policy Research Institute, 2022)
Global food, fuel, and fertilizer prices have risen rapidly in recent months, driven in large part by the fallout from the ongoing war in Ukraine and the sanctions imposed on Russia. Other factors, such as export bans, have also contributed to rising prices. Palm oil and wheat prices increased by 56 and 100 percent in real terms, respectively, between June 2021 and April 2022, with most of the increase occurring since February (Figure 1). Wide variation exists across products, with real maize prices increasing by only 11 percent and rice prices declining by 13 percent. The price of crude oil and natural gas has also risen substantially, while the weighted average price of fertilizer has dou-bled. With these changes in global prices, many developing countries and their development part-ners are concerned about the implications for economic stability, food security, and poverty.